Meluruskan Beberapa Persepsi tentang Poligami (Tafsir Surah al-Nisa Ayat 3 dan 129) - Saguni, Muhammad Kasim; Syandri, Syandri (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2018)
This study describes some false perceptions of polygamy based on the Qur'an Chapter An-NisÄ ' verse no. 3 and 129. The method used in this study is library research. Various sources were collected to obtain data and facts. These data were collected sorted and selected and then analyzed to answer the first two main subjects: understanding and history of polygamy, second: correcting some of the wrong perceptions about polygamy. The results of this study indicate that polygamy is the marriage of a man with more than one woman, which has been widely known and practiced by the Muslim in various parts of the world. As for the false perception, the false perceptions are caused by lack of proper understanding about pure religious teachings according to the Qur'an, the Sunnah of the Prophet and the understanding of zealous and pious Islamic scholars. Another cause is due to the a priori behavior and lust. Moreover, the Muslim haters take advantage over te issue of polygamy to insult Islam with various heinous accusations where these insults coming from hate speech and dishonesty in judging this issue.